Analysis of the Activities of Young Leaders in Enterprise Management - Kholiqulov, A. N.; Burkxonov, B. S. (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
In this article, the enterprise management system and the system of bodies all aspects of national importance, management training, re-training and improving their skills on the ongoing reforms in the country and keep in mind the analysis of their business activities.